PENGARUH FASILITAS BELAJAR DAN PERAN GURU TERHADAP HASIL BELAJAR ONLINE SISWA - Ani Setiani; Yudho Ramafrizal S; Leni Maryani; Veri Aryanto Sopiansah; Deden Regito (Oikos : Jurnal Ekonomi dan Pendidikan Ekonomi, 2022)
This study aims to determine the effect of learning facilities and the role of teachers on online learning outcomes in odd semester economic subjects in class X BDP SMK Pasundan 4 Bandung. The method used in this research is a survey. The subjects in this study used a sample of 56 students. Analysis of the data used is descriptive analysis, classical assumption test and hypothesis testing through multiple linear regression calculation and coefficient of determination with the help of SPSS 25.0 for Windows. From the results of research using descriptive analysis, it is obtained that the average score recapitulation of respondents regarding learning facilities is in the "undecided" category, indicated by an average weight of 3.11 with a percentage of 62.40%. This indicates that most of the students are hesitant about learning facilities according to the average respondent. Meanwhile, regarding online learning outcomes, students are in the "Strongly Agree" category, indicated by an average weight of 4.50 with a percentage of 89.20%. This indicates that most students strongly agree that students' online learning outcomes increase according to the average respondent. Based on the classical assumption test through the normality test that has been carried out, it is obtained a significant value of 0.200> 0.05, it can be concluded that the residual value is normally distributed. In the hypothesis test, multiple linear regression coefficients (Y= 1.638 – 0.513X1 + 0.577X2 + 0.347) which means that if learning facilities (variable X1) and the role of teachers (variable X2) increase, it will cause a tendency to increase student online learning outcomes (variable X2). Y) of 1.09. The contribution of the influence given by the learning facilities variable to students' online learning outcomes is 34.5% and the teacher's role variable to students' online learning outcomes is 35.8%, the percentage is calculated based on the results of the calculation of the coefficient of determination is 70.3%, while the rest amounted to 29.7% influenced by external factors that were not examined by the researcher, and the conclusion was acceptable. As the end of the research, the author conveys suggestions for schools for learning facilities and teachers to use adequate learning facilities in the ongoing teaching and learning process, specifically on learning facilities and the role of teachers in general so as to improve student online learning outcomes.